2007
DOI: 10.1007/s11701-007-0017-y
|View full text |Cite
|
Sign up to set email alerts
|

Transition from open to robotic-assisted radical prostatectomy is associated with a reduction of positive surgical margins amongst private-practice-based urologists

Abstract: Several recent studies have suggested that thought leaders in radical prostatectomy have decreased their own positive margin rates by switching from open to robot-assisted radical prostatectomy. Theoretically, this improvement is largely attributed to enhanced visualization of the deep pelvis and precision of dissection afforded by the instrumentation. To date, it has not been determined if this phenomenon exists amongst non-fellowship-trained urologists in private practice. Herein, we describe the positive ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…If one uses positive margins as a surrogate marker for a higher likelihood of prostate cancer recurrence, one can imagine that the lower positive margin rate previously described in this community after the transition to RARP may translate into lower rates of adjuvant pelvic radiation therapy, androgen blockade, imaging, and other ancillary cost, thus reaping greater savings in the future. 7 With regard to surgical training, we have had to modify our training techniques significantly so that residents can learn to perform robot-assisted surgery while maintaining patient safety. The exact techniques used to accomplish this have been previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If one uses positive margins as a surrogate marker for a higher likelihood of prostate cancer recurrence, one can imagine that the lower positive margin rate previously described in this community after the transition to RARP may translate into lower rates of adjuvant pelvic radiation therapy, androgen blockade, imaging, and other ancillary cost, thus reaping greater savings in the future. 7 With regard to surgical training, we have had to modify our training techniques significantly so that residents can learn to perform robot-assisted surgery while maintaining patient safety. The exact techniques used to accomplish this have been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…We now, however, have up to 7-year follow-up data for several mature series showing equivalent, and in some cases improved, oncologic and functional results in addition to lower complication rates. 7,23,24 For better or for worse, we predict that at some point in the future, many surgeons will not be able to perform open radical prostatectomy when robot-assisted surgery is inappropriate or impossible because of adhesions from previous surgery. These patients may need referral to an open surgical specialist to have an open prostatectomy performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a statistically signiWcant lower incidence PSM in patients undergoing RALP; the most common location of a PSM in both RALP and ORP cases was the apex. Madeb et al [10] also reported that the transition from open to robot-assisted radical prostatectomy was associated with a reduction in PSM rates amongst privatepractice-based urologists; they suggested that the improvement is largely attributed to enhanced visualization of the deep pelvis and increased precision of dissection aVorded by the instrumentation.…”
Section: Discussionmentioning
confidence: 99%